The role of rare earth elements and dietary intake in tongue cancer: a mediation analysis in southeast China - Wang, Na; Liu, Fengqiong; Chen, Yujia; Xie, Manling; Gao, Bingju; Qiu, Yu; Lin, Lisong; Shi, Bin; Chen, Fa; He, Baochang (Frontiers in Public Health, 2023)
Objective The current research aimed to examine how dietary intake and rare earth elements may affect the development of tongue cancer. Methods The levels of serum ten rare earth elements (REEs) in 171 cases and 171 healthy matched controls were measured by inductively coupled plasma mass spectrometry (ICP-MS). The conditional logistic regression was used to examine the relationship between dietary intake, serum levels of ten REEs and tongue cancer. Mediation effect and multiplicative interaction analysis were then performed to estimate the potential contribution of REEs in dietary intake associated with tongue cancer. Results Compared with the control group, patients with tongue cancer consumed significantly less fish, seafood, fruit, green leafy vegetables, and non-green leafy vegetables, and with higher serum praseodymium (Pr), dysprosium (Dy), and lanthanum (La) levels and lower serum cerium (Ce), scandium (Sc) levels. The interaction effect was observed between some REEs and food categories. Green vegetables' impact on the risk of tongue cancer is partially attributed to the La and Thorium (Th) elements they contained (P<0.05, the mediated proportion were 14.933% and 25.280%, respectively). The effect of non-green leafy vegetables for tongue cancer mediated via Pr, Dy, and Th (P<0.05, the mediated proportion were 0.408%, 12.010%, and 8.969%, respectively), and the Sc components in seafood (P<0.05, the mediated proportion was 26.120%) is partly responsible for their influence on the risk of tongue cancer. Conclusion The correlation between REEs and dietary intakes for tongue cancer is compact but intricate. When influencing tongue cancer, a few REEs work in conjunction with food categories while some work as a mediator.